Evaluasi User Interface pada Game Elmer & Minda Menggunakan Metode Usability Testing - Wichdan Bawariq Prawirayudha; Husein Azka Effendi; I Made Prema Bimamukti; Ananta Miyoru Wijaya; Salsabhilla-Anggraeni Wardani (CV. Ulil Albab Corp, 2022)
Today’s technology development has advanced very rapidly. Various innovations began to be produced to assist humans in their everyday lives. It also comes across in the creative industry, where games are one of the emerging trends along with technological advancements. In addition, technological developments affect the emergence of more high-quality games in terms of concepts, mechanics, art, and supporting sound. However, it is still common for some users to have trouble understanding the games’ layout and menus. Therefore, it is necessary to evaluate the UI/UX feature of each game that has been made. In this study, the researcher will evaluate the Elmer & Minda game, a coded logic-based puzzle-platformer game. The research aims to determine whether the user interface of the Elmer & Minda game adheres to the user needs principle. The research was conducted by analyzing usability tests from the user interface display so that evaluation can be performed to improve the user experience when playing the Elmer & Minda game